MS. MARVEL AS A REPRESENTATION OF THE STRUGGLE FOR AMERICAN IDENTITY - Ashika Prajnya Paramita (Rubikon : Journal of Transnational American Studies, 2016)
In early 2014, Marvel Comics released a new series called Ms. Marvel. The main character of this series is a Pakistani-American Muslim girl named Kamala Khan. Her story is a breakthrough against the negative representation of Islam in the Western world, especially after 9/11. This research examines five issues taken from the first volume of the Ms. Marvel comic book series. The paper discusses the reason why this series is substantial in the struggle of Muslim immigrants to survive as a minority group in the United States. The results show that Ms. Marvel serves as a medium of communication for the under-represented American Muslim community. Furthermore, by accepting the new superhero, the American society itself has also transformed and it is beginning to adapt to the idea that Muslim immigrants are members of their society.Keywords: Muslim, superhero, comic book, identity, popular culture